A cloud platform for space science mission concurrent design. (March 2018) - Deng, Li; Yang, Zhen; Du, Pengyu; Song, You
Using concurrent design methodology, the duration of space science mission in conceptual design phase can be shortened. This approach requires hardware and software resources to support, such as professional design tools and concurrent design environment. Except for the professional groups, the general researchers such as teachers and students have no chance to access these resources. Nowadays, more and more researchers distributed in different locations join into the space science research. The need for an open concurrent design platform offering design tools and data sharing environment has increased. This article presents a Cloud Platform of Concurrent Design for Space Science Mission. This Cloud Platform of Concurrent Design for Space Science Mission uses the idea of Software as a service, in which five design and analysis tools are offered as services to satisfy the basic requirements for space science mission concurrent design in conceptual design phase. This cloud platform provides the access to space science mission concurrent design for expert and non-expert users using a thin client of web browser. This article presents the platform architecture of the Cloud Platform of Concurrent Design for Space Science Mission and five software offered as services. The services include spacecraft conceptual orbit design, structure design, payload coverage analysis, data transmission analysis, and virtual community. And the basic cloud service (computing and storage) is also briefly introduced. It is described in detail how these services can be leveraged by users to do the concurrent design for one space science mission.